Pengaruh Pemberian Propofol Intravena 10mg/KgBB, 25 mg/KgBB dan 50 mg/KgBB Terhadap Ekspresi Kaspase 3 Hipokampus pada Mencit Balb/ C Dengan Cedera Kepala - Yusriyani; Sudjito, Mulyo Hadi; Murti, Bhisma (Jurnal Kedokteran Indonesia, 2012)
Background:Head injury is one of the leading causes of death and disability. In head injury there is biomolecularand biochemical pathologic process that can cause necrosis and apoptosis via caspase 3 activation. Propofol is an intravenous anesthetic drug that has neuroprotective mechanism by regulating caspase 3. This study aimed to determine the inhibitory effect of intravenous propofol 10 mg/kgBW, 25 mg/kgBW and 50 mg/kgBW oncaspase 3expression in mice balb/c with head injury. Methods: This was a laboratory experiment using randomized controlled trial design. Asample of 32 Balb/c mices were divided into 4 groups. All groups underwent head injury procedure using weight drop technique. Group 1 did not received propofol. Group 2, 3, and 4 received intravenous 10 mg, 25 mg, and 50 mg/kgBB propofol, respectively. Caspase 3 activation was stained and identified by immunohistochemical technique 6 hours afteradministration of propofol. Difference in mean between groups was tested by One Way Anova and mean pair-wise groups by Post Hoc Test on SPSS 12. Results: Mean caspase 3 expresion in each group was as follow: Group 1=4.08, Group 2= 2.95, Group 3= 2.52, Group 4=1.77. One way Anova showed statistically significant difference in mean caspase 3 expression between groups (p<0.001). The higher dose of propofol, the lower caspase 3. The pair-wise mean difference were as followsGroup1-Group2 (p<0.001), Group1-Group3 (p<0.001), Group1-Group4 (p<0.001), Group2-Group4 (p<0.001), Group3-Group4 (p<0.001), and Group2-Group3 (p=0.232). Conclusion:Administration of intravenous propofol with 10,25,50 mg/kgBW doses were effective to inhibit caspase 3 activity expression in mices with head injury. Higher doses give stronger inhibitory effect, with 50mg/kgBW being the recommended optimal dose. Keywords: caspase 3 expression, propofol, mice, head injury